Ш.СЕЙТОВ РОМАНЛАРЫНЫӉ ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА ИЗЕРТЛЕНИЎИ («Халқабад» романы мысалында) - Бекбергенова, З.У. (FAN va JAMIYAT, 2020)
The article provides the analysis of scientific articles on the tetralogy «Khalkabad» by Sh. Seitov, consisting of four voluminous books published during the years of independence in the journals «Amu Darya», «Vestnik» of Karakalpak branch of the Academy of Sciences of the Republic of Uzbekistan, «Vestnik» of KSU and the corresponding conclusions are made.